Dimension stone of Makawanpur District, central Nepal (Journal of Nepal Geological Society, 2003)
An exploration of polished/dimension stones was carried out in the Makawanpur district. In the study area various rock types were examined for their suitability in terms of quality and strength, and potential areas were delineated for the detailed study. The area is found to comprise various rock types suitable for dimension stones. Among them, the most viable rock types are granite, aplite, marble, limestone, quartzite and amphibolite. This paper describes mineralogy, weathering grade, nature of discontinuities, and physico-mechanical properties of rocks from different potential sites and presents the results of exploration.